Paramedics! : test yourself in pathophysiology - Rogers, Katherine (Open University Press, 2011)
This self-test book of self-assessment questions and quizzes that is designed to both test paramedic students learning pathophysiology and help them understand their knowledge gaps by explaining the answers to the questions included.